DIET IMPACT ON ORAL HEALTH AND ENDOTHELIAL FUNCTION - Ruxandra Maria Hurjui; Ion Andrei Hurjui; Giulia Mihaela Pînzariu; Tudor Cojocaru; Andrei Neamțu (Romanian Society of Oral Rehabilitation, 2022)
Since many years ago a lot of studies conclude that the components of the human body are closely interdependent; as a result, disease conditions in some organs or components can influence the development of disease in other body locations. The effect of oral health upon health in general has been investigated for decades by many epidemiological studies. That is why, there appears to be a clear relationship between deficient oral health and different systemic disorders such as cardiovascular disease and metabolic syndrome. The precise relationship between them is the subject of ongoing research, and a variety of theories have been proposed, though most of them postulate the mediation of an inflammatory response. This association between the oral cavity diet and endothelial function in general requires further study, and health professionals should mark the importance of adopting measures destined to promote correct oral health.